Application of Simultaneous Oil Extraction and Transesterification in Biodiesel Fuel Synthesis: A Review - Violeta Makareviciene; Egle Sendzikiene; Milda Gumbyte (Energies, 2020)
Increasing concentrations of greenhouse gases in the atmosphere are leading to increased production and use of biofuels. The industrial development of biodiesel production and the use of biodiesel in the EU transport sector have been ongoing for almost two decades. Compared to mineral diesel production, the process of producing biodiesel is quite complex and expensive, and the search for new raw materials and advanced technologies is needed to maintain production value and expand the industrial production of biodiesel. The purpose of this article is to review the application possibilities of one of the new technologies—simultaneous extraction of oil from oily feedstock and transesterification (in situ)—and to evaluate the effectiveness of the abovementioned process under various conditions.